PORTARIA PRR4 Nº 04, DE 03 DE JANEIRO DE 2001 - Carlos Eduardo Thompson Flores Lenz (BSMPF, Brasília, DF, 1. quinzena jan. 2001., 2001)
Designa a servidora MÁRCIA SANTANA para exercer a função de Secretária de Procurador, FC-02.